Analisis Profiling Pelaku, Motif Pelaku dan Dampak Yang Ditimbulkan Dari Tindakan Gratifikasi Rafael Alun Trisambodo - Herlina Yuliyanti; Lissa Rahmawati; Nera Marinda Machdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Profiling of corrupt perpetrators is done by looking for information such as office or profession, educational level, employment history and criminal background. Because increased tax receipts are not proportionate to the extraction of benefits to the public, it creates mistrust and reluctance to meet tax obligations. It endangers national security in many aspects, such as social, cultural, moral, political, and legal. Literature Review is an in-depth study of a particular topic with a qualitative approach. The purpose of this writing is to discuss and analyze further about the profiling of perpetrators and the massive impact caused by the case of Rafael Alun Trisambodo PNS class III in the General Directorate of Tax Kemenkeu who served as Head of the General Division of Kanwil DJP South Jakarta. His motive for corruption and money laundering was to enrich himself, his family, or anyone else by abusing office. The conclusion of this writing is that efforts to combat corruption are still not optimal as many sides tempt wealth and take advantage of opportunities.